2000
DOI: 10.1017/s0014479700001071
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shade on Stomatal Density, Leaf Size and Other Leaf Characteristics in the Major Tropical Root Crops, Tannia, Sweet Potato, Yam, Cassava and Taro

Abstract: S U M M A R YSince shading often occurs under normal growing conditions in various cropping systems (for example, intercropping, alley cropping), field experiments were carried out to determine the effects of shading on stomatal density, leaf size, leaf dry matter, and leaf lamina thickness in the major tropical root and tuber crops, tannia (Xanthosorna sa&ifooliurn), sweet potato (Zpornoea batatas), yam (Dioscorea esculenta), cassava (Manihot esculenta), and taro (Colocasia esculenta). Shading decreased stoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 9 publications
5
29
0
3
Order By: Relevance
“…Johnston and Onwueme (1998) concluded that, among five major tropical tuber crops, cocoyam (Xanthosoma sagittifolium) and taro were particularly well adapted to shade. They also found that leaves of taro grown in shade were larger and thinner than when cultivated in full sun (Onwueme and Johnston 2000); in our study, taro grown under trees produced an greater number of leaves. It thus seems that C3 plant reactions to shade, to some degree, reflect their role in natural ecosystems.…”
Section: Discussionsupporting
confidence: 73%
“…Johnston and Onwueme (1998) concluded that, among five major tropical tuber crops, cocoyam (Xanthosoma sagittifolium) and taro were particularly well adapted to shade. They also found that leaves of taro grown in shade were larger and thinner than when cultivated in full sun (Onwueme and Johnston 2000); in our study, taro grown under trees produced an greater number of leaves. It thus seems that C3 plant reactions to shade, to some degree, reflect their role in natural ecosystems.…”
Section: Discussionsupporting
confidence: 73%
“…This higher efficiency of taro, a C 3 photosynthesis pathway plant, in shade conditions can be explained by increasing leaf size, chlorophyll content per unit area and stomatal density in their leaves (Johnston and Onwueme 1998;Onwueme and Johnston 2000). Despite its photosynthetic efficiency in shaded conditions, taro plants growth may be affected when competing for nutrients and water with trees because of its high requirement for these growth resources (Bussel and Bonin 1998;Onwueme 1999).…”
Section: Crops Studiedmentioning
confidence: 99%
“…Penelitian (Aliyu dkk., 2015) menyatakan bahwa proses pemangkasan dapat mempercepat proses pembungaan mencapai 50% lebih cepat dibandingkan dengan tanaman okra yang tidak dipangkas. Perlakuan pemangkasan dapat meminimalisir adanya Organisme Pengganggu Tanaman (OPT) (Iremiren, 1987).…”
Section: J Agro Complex 2(2)unclassified
“…Lingkar Batang Okra Merah pada Perlakuan Dosis Pemupukan Kompos Serasah yang Berbeda dan Pemangkasan Dosis pupuk kompos serasah (Kg N/ha) Pemangkasan Rata -rata Tidak dipangkas (P1) Dipangkas (P2) Iremiren (1987) pemangkasan sangat membantu tanaman dalam hal fotosintesis, karena pemangkasan pada pucuk tanaman membantu sinar matahari kesuluruh tanaman sehingga proses fotosintesis lebih maksimal. Pemangkasan membantu tanaman okra untuk merangsang produksi dan pengembangan daun agar aktivitas fotosintesis berlangsung secara efisien (Aliyu, 2015).…”
Section: Jumlah Daununclassified